ANALISA KUALITAS FISIK PEMBANGUNAN INFRASTRUKTUR JALAN USAHA TANI DESA PADA PROGRAM KETAHANAN PANGAN DANA DESA (KECAMATAN TANJUNG LUBUK KABUPATEN OGAN KOMERING ILIR) - Novianti, Nensi (Fakultas Teknik Universitas Muhammadiyah Sumatera Barat, 2025)
This study analyzes the physical quality of agricultural road construction in four villages in Tanjung Lubuk District, Ogan Komering Ilir Regency, in the village fund food security program. The methods used include a questionnaire survey to measure community and village apparatus satisfaction and a Hammer Test to assess the quality of road concrete. The results of the study indicate that although the community is generally satisfied with the road construction, the quality of the concrete produced is still below the established standards (SNI 03-6468-2000 and ACI 318), with an average compressive strength value of 10 MPa. The main factors influencing the low quality of roads include a lack of technical understanding in concrete mixing, weak supervision, and limited resources in the construction process carried out independently by the community. Some common damages found include sinking, release of aggregate grains, and longitudinal cracks. Therefore, increased supervision, technical education for workers, and better road maintenance are needed so that the infrastructure built can be more durable and beneficial to the community.Keywords: Concrete Quality, Village Road Infrastructure, Community Satisfaction, Hammer Test, Construction Supervision